Microencapsulação por gelificação iônica e interação eletrostática do corante de buriti (Mauritia flexuosa L. f.) - Aranha, Caroline Pereira Moura [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this work was to study the microencapsulation process by ionic gelation associated with the electrostatic interaction of the dye extracted from the buriti pulp. Initially the surface tension, density and rheological properties of the solutions of alginate and pectin, and buriti oil emulsions, were determined. For the ionic gelation step, two alternative biopolymers were tested: alginate and amidated low-methoxyl pectin, both being gelled in the presence of calcium ions. As core material was used buriti oil, which was extracted from the palm fruits by the Bligh-Dyer method. The produced microcapsules were coated by electrostatic interaction with whey protein concentrate (WPC). The proteins conditions for the adsorption of on the surface of alginate or pectin particles were determined by the Zeta potential analysis of the dispersions of protein and polysaccharides. This analysis also gave the isoelectric point of the whey proteins. The atomization process for ionic gelation was carried out at different conditions of air and feed flow rate. The influence of these parameters on the characteristics of buriti oil microparticles produced with alginate:WPC and pectin:WPC was evaluated by determining: the dimensionless numbers (Reynolds, Weber and Ohnesorge); the average particle diameter obtained by ionic gelation only and after interaction with WPC; the encapsulation efficiency and carotenoid retention; and color parameters (a*, b*, L*, C and h). From these results, four best conditions of the atomization process to each pair of polymers studied were selected. The particles produced using the selected conditions were evaluated regarding the mean diameter after lyophilization, the FTIR-ATR and morphology using microscopy: optical, scanning electron and confocal laser. The capsules showed high encapsulation efficiency and carotenoids retention, however showed no difference in their coloring ...

O objetivo deste trabalho foi estudar o processo de microencapsulação por gelificação iônica associada à interação eletrostática do corante extraído da polpa de buriti. Primeiramente realizou-se a determinação da tensão superficial, propriedades reológicas e densidade das dispersões de alginato e pectina e suas emulsões com azeite de buriti. Para a etapa de gelificação iônica foram avaliadas duas alternativas de biopolímeros: alginato e pectina de baixo teor de esterificação amidada, sendo ambos gelificados na presença de íons cálcio. Como material de recheio foi utilizado o azeite de buriti, o qual foi extraído dos frutos pelo método de Bligh-Dyer. Em seguida, as microcápsulas produzidas foram recobertas, por interação eletrostática, com concentrado de proteínas do soro de leite (WPC). As condições de adsorção das proteínas na superfície das partículas de alginato ou de pectina foram definidas pela análise do potencial Zeta das dispersões de proteína e de polissacarídeos. Com esta análise também se encontrou o ponto isoelétrico das proteínas do soro de leite. O processo de atomização para gelificação iônica foi realizado com diferentes valores de vazão de ar comprimido e de alimentação. A influência desses parâmetros nas características das micropartículas de azeite de buriti produzidas com alginato:WPC e pectina:WPC foi avaliada pelas determinações: dos números adimensionais (Reynolds, Weber e Ohnesorge); do diâmetro médio das partículas obtidas somente pela gelificação iônica e após a interação com WPC; da eficiência de encapsulação e retenção de carotenoides; e dos parâmetros de cor (a*, b*, L*, C e h). A partir dos resultados foram selecionadas as quatro melhores condições do processo de atomização, para cada par de polímeros estudados. As partículas produzidas a partir das condições selecionadas foram avaliadas em...
Keywords: Tecnologia de alimentos; Microencapsulação; Buriti; Alginatos; Pectina; Soro do leite; Atomização